Evaluation of Biocompatibility and Administration Site Reactogenicity of Polyanhydride‐Particle‐Based Platform for Vaccine Delivery. Issue 2 (26th September 2012) - Huntimer, Lucas; Ramer‐Tait, Amanda E.; Petersen, Latrisha K.; Ross, Kathleen A.; Walz, Katherine A.; Wang, Chong; Hostetter, Jesse; Narasimhan, Balaji; Wannemuehler, Michael J.
Abstract Efficacy, purity, safety, and potency are important attributes of vaccines. Polyanhydride particles represent a novel class of vaccine adjuvants and delivery platforms that have demonstrated the ability to enhance the stability of protein antigens as well as elicit protective immunity against bacterial pathogens. This work aims to elucidate the biocompatibility, inflammatory reactions, and particle effects on mice injected with a 5 mg dose of polyanhydride nanoparticles via common parenteral routes (subcutaneous and intramuscular). Independent of polymer chemistry, nanoparticles more effectively disseminated away from the injection site as compared to microparticles, which exhibited a depot effect. Using fluorescent probes, the in vivo distribution of three formulations of nanoparticles, following subcutaneous administration, indicated migration away from the injection site. Less inflammation was observed at the injection sites of mice‐administered nanoparticles as compared to Alum and incomplete Freund's adjuvant. Furthermore, histological evaluation revealed minimal adverse injection site reactions and minimal toxicological effects associated with the administration of nanoparticles at 30 days post‐administration. Collectively, these results demonstrate that polyanhydride nanoparticles do not induce inflammation as a cumulative effect of particle persistence or degradation and are, therefore, a viable candidate for a vaccine delivery platform.